Post Hoc Analyses of Data from a 90-Day Clinical Trial Evaluating the Tolerability and Efficacy of Tapentadol Immediate Release and Oxycodone Immediate Release for the Relief of Moderate to Severe Pain in Elderly and Nonelderly Patients. (2011) - Vorsanger, Gary; Xiang, Jim; Biondi, David; Upmalis, David; Delfgaauw, Jacqueline; Allard, René; Moskovitz, Bruce
Abstract : OBJECTIVE: To evaluate the tolerability and efficacy of tapentadol immediate release (IR) and oxycodone IR for relief of moderate to severe pain in elderly and nonelderly patients. METHODS: Post hoc data analyses were conducted on a 90-day randomized, phase 3, double-blind, flexible-dose study (ClinicalTrials.gov: NCT00364546) of adults with moderate to severe lower back pain or osteoarthritis pain who received tapentadol IR 50 mg or 100 mg, or oxycodone HCl IR 10 mg or 15 mg every 4 h to 6 h as needed for pain relief. Treatment-emergent adverse events and study discontinuations were recorded. RESULTS: Data from 849 patients randomly assigned (4:1 ratio) to treatment with a study drug (tapentadol IR [n=679] or oxycodone IR [n=170]) were analyzed according to age (younger than 65 years of age [nonelderly], or 65 years of age or older [elderly]) and treatment group. Among elderly patients, incidences of constipation (19.0% versus 35.6%) and nausea or vomiting (30.4% versus 51.1%) were significantly lower with tapentadol IR versus oxycodone IR (all P<0.05). Initial onsets of nausea and constipation occurred significantly later with tapentadol IR versus oxycodone IR (both P≤0.031). Tapentadol IR-treated elderly patients had a lower percentage of days with constipation than oxycodone IR-treated patients (P=0.020). For tapentadol IR- and oxycodone IR-treated elderly patients, respectively, incidences of study discontinuation due to gastrointestinal treatment-emergent adverse events were 15.8% and 24.4% (P=0.190). Tapentadol IR and oxycodone IR provided similar pain relief, with no overall age-dependent efficacy differences (mean pain scores [11-point numerical rating scale] decreased from 7.0 and 7.2 at baseline, to 4.9 and 5.2 at end point, respectively). CONCLUSIONS: Tapentadol IR was safe and effective for the relief of lower back pain and osteoarthritis pain in elderly patients, and was associated with a better gastrointestinal tolerability profile than oxycodone IR.